Different operators via weighted averaging and geometric approach using trigonometric neutrosophic interval-valued set and its extension - Raed Hatamleh; Ahmed Salem Heilat; M.Palanikumar; Abdallah Al-Husban (Neutrosophic Sets and Systems)
This work presents a new method for generating tangent trigonometric neutrosophic interval-valued sets. This article will cover tangent trigonometric neutrosophic interval-valued weighted averaging, geometric, generalized notions. We used an aggregating model to get the weighted average and geometric. Several sets with substantial characteristics will be further studied using the algebraic techniques.